Review of magnetorheological fluids and nanofluids thermal behaviour. Issue 1 (November 2015) - Rahim, M S A; Ismail, I
Abstract: Magnetorheological fluids are smart materials with the capability to reversibly change from liquid to near solid state under the presence of external magnetic fields. The interest in magnetorheological fluid as a heat transfer medium is due to the possibility of controlling its flow and heat transfer process through external magnetic field. This review highlights on the recent developments of magnetorheological fluid and nanofluid in the field of thermal behaviour. Special emphasis is paid to the understanding of their thermal conductivity property by several parameters which include particle volume fraction, shape and size of particles, materials of particles and base fluid, and magnetic field. Reports indicate that the increase with particle volume fraction and magnetic field strength may increase the thermal conductivity of magnetorheological fluid. From the theory and experimental given, relationship between these parameters and thermal conductivity can be found.